2018
DOI: 10.1038/s41431-018-0271-7
|View full text |Cite
|
Sign up to set email alerts
|

Fetal fraction evaluation in non-invasive prenatal screening (NIPS)

Abstract: An important factor in quality control of non-invasive prenatal screening (NIPS) or testing (NIPT) is a sufficient percentage of fetal DNA to avoid false-negative results. Here we evaluate 14,379 shallow whole-genome sequenced diagnostic NIPS samples, as well as negative controls, for both technical and biological factors that can influence fetal fraction and its assessment. Technically, bioinformatics analyses can have a profound impact on fetal fraction determination. We found best performance for fetal frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 21 publications
5
49
0
Order By: Relevance
“…However, the methods used to measure FF vary considerably and are not directly comparable, leading to calls for industry standardization in methods and reporting . While Y chromosome‐based methods appear to be the closest to an accepted “gold standard" in this field, these are obviously limited by their applicability to only those pregnancies with a male fetus. Some advocate using a combination of methods to check for the presence of fetal cfDNA and FF calculation for female and male bearing pregnancies .…”
Section: Clinical Laboratory Aspects Of Ffmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the methods used to measure FF vary considerably and are not directly comparable, leading to calls for industry standardization in methods and reporting . While Y chromosome‐based methods appear to be the closest to an accepted “gold standard" in this field, these are obviously limited by their applicability to only those pregnancies with a male fetus. Some advocate using a combination of methods to check for the presence of fetal cfDNA and FF calculation for female and male bearing pregnancies .…”
Section: Clinical Laboratory Aspects Of Ffmentioning
confidence: 99%
“…They have been previously thoroughly reviewed by Peng and colleagues . Several attempts to compare different FF algorithms have been published that highlight the significant variation between methods . It is now apparent that individual clinical laboratories should optimize their platform‐specific FF methods according to their lower LOD, and not rely on arbitrary FF cutoff values for quality control.…”
Section: Clinical Laboratory Aspects Of Ffmentioning
confidence: 99%
“…The responses are summarized in Table 4 below. Two respondents indicated that they would offer termination of pregnancy for a very high risk [1,7] on FTS.…”
Section: Recommendations At Various Fts Risk Levelsmentioning
confidence: 99%
“…For instance, a foetal fraction of at least 4% is essential for a reportable result. A low foetal fraction is more likely in certain populations such as obese women and those with certain aneuploidies [6][7][8], and these facts need to be incorporated into pre and post-test counselling.…”
Section: Introductionmentioning
confidence: 99%
“…While z scores are used for evacuating risk of aneuploidy of chromosome 13, 18 and 21, fetal fraction (FF) of cell free DNA is also considered critical to the results [7,8]. FF is based on the sequencing results of NIPS and is calculated using chrY concentration or algorithms of generalized linear regression such as seqFF [9]. It is conformed that FF lower than 3.5%-4% is a key factor may cause no-call reports or false positive and negative results [10,11].…”
Section: Introductionmentioning
confidence: 99%